Cloud computing and services science : 8th International Conference, CLOSER 2018, Funchal, Madeira, Portugal, March 19-21, 2018, Revised selected papers /: 8th International Conference, CLOSER 2018, Funchal, Madeira, Portugal, March 19-21, 2018, Revised selected papers. (2019) - Unknown
No abstract available